Developing a model of tank cooling by water jets from hydraulic monitors under conditions of fire - Abramov, Yuriy; Basmanov, Oleksii; Salamov, Javid; Mikhayluk, Andrey; Yashchenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
The main danger of a fire at an oil storage tank farm lies in its cascade spreading to neighboring tanks. This happens due to heating metal structures to the temperature of self-ignition of vapors of petroleum products. That is why cooling tanks is a priority in the localization of such fires. One of the most reliable methods of cooling is water feeding onto the tank walls using hydraulic monitors that are stationed outside the banking. In this case, the problem is to calculate the cooling action of water and to determine such parameters of its supply that would ensure cooling tank structures to a safe temperature. The model of the water jet motion after exiting the nozzle of a firefighting barrel was constructed. The algorithm of water supply by using a hydraulic monitor, which provides consistent alternation of the water jet motion on the tank wall in the horizontal and vertical direction was proposed. The model of cooling action of the water film formed after water jet hitting the wall of the tank was constructed. The model is based on heat balance equations for a tank wall and a water film and takes into consideration the periodic water jet motion on a tank wall. When constructing heat balance equations, we took into consideration convective and radiant heat exchange with a fire and the environment. It was shown that the temperature distribution on the tank wall and the water film is described by the system of two nonlinear differential equations of the first order. The findings obtained in the study make it possible to determine the parameters of water supply, which provide tank cooling to a safe temperature